INTENSITY OF PARENTAL COMMUNICATION METHODS IN BEHAVIORAL AND EMOTIONAL MATURITY IN CHILDRENS AT AISYIYAH BUSTANUL ATHFAL 13 KINDERGARTEN, MALANG CITY - Yulia, Nikmahtul Khoir Tri (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2025)
Parental behavioral and emotional development is driven by uncomfortable situations. Actions often irrational when emotions arise. This, of course, impacts the surrounding environment, particularly the family environment, including the impact felt by children during their development. The research methodology used was quantitative with a correlative approach. Data collection techniques included surveys, interviews, instruments, and discussion sessions. The results showed that parental behavior and emotions determine the growth of synapses in children's brains. Parents play a role as mediators in children's development. Findings from six indicators indicate that parental emotional maturity influences children's emotional development at home, with an average ratio of 21.5% to 39.5%. Meanwhile, indicators of parental behavioral maturity that impact children's behavioral development show an average ratio of 20.66% to 41.32%. This requires a management strategy at various stages through displacement techniques, cognitive adjustment techniques, and coping techniques. A comfortable and warm family environment will have a relationship with small changes in children. In the learning process, children not only get to know themselves but also learn about how to behave and manage their emotions through expressions and body gestures. Furthermore, the intensity of parental communication will help foster healthy bonds in children from an early age. Parents also serve as role models for children throughout their development and into adulthood. The environment has a significant influence on children's behavioral and emotional changes.